Diabetick á autonomní neuropatie - Boucek, P (Vnitrni lekarstvi, 1989)
Affection of the vegetative nervous system is a relatively frequent and often serious complication of diabetes. The aetiopathogenesis of diabetic autonomous neuropathy has not been reliably explained so far, most probably metabolic changes are involved resulting from prolonged hyperglycaemia. A part played by other e.g. congenital factors cannot be ruled out. Autonomous neuropathy can influence the function of the cardiovascular, digestive, urogenital and other systems and cause difficult diagnostic and therapeutic problems. Examinations should comprise also simple tests of cardiovascular reflexes. Preventive effects can be expected also from long-term optimal metabolic compensation of patients; some recently tested preparations interfere with pathobiochemical mechanisms. At the same time opportunities of symptomatic therapy are markedly extended at present.
Keywords: diabetické neuropatie; Autonomic Nervous System Diseases; Diabetic Neuropathies; Humans; lidé; nemoci autonomního nervového systému